An update on advanced therapies for Parkinson's disease: From gene therapy to neuromodulation - Serva, Stephanie N.; Bernstein, Jacob; Thompson, John A.; Kern, Drew S.; Ojemann, Steven G. (Frontiers in Surgery, 2022)
Advanced Parkinson’s disease (PD) is characterized by increasingly debilitating impaired movements that include motor fluctuations and dyskinesias. At this stage of the disease, pharmacological management can result in unsatisfactory clinical benefit and increase the occurrence of adverse effects, leading to the consideration of advanced therapies. The scope of this review is to provide an overview on currently available therapies for advanced PD, specifically levodopa-carbidopa intestinal gel (LCIG), continuous subcutaneous apomorphine infusion (CSAI), radiofrequency (RF) ablation, stereotactic radiosurgery (SRS), MRI-guided focused ultrasound (MRgFUS), and deep brain stimulation (DBS). Therapies in clinical trials are also discussed, including novel formulations of subcutaneous carbidopa/levodopa, gene-implantation therapies, and cell-based therapies. This review focuses on the clinical outcomes and adverse effects of the various therapies, and also considers patient-specific characteristics that may influence treatment choice. This review can equip providers with updated information on advanced therapies in PD to better counsel patients on the available options.